(untitled) (Damascus University Journal of agriculture sciences, 2022)
This study was carried out in the Department of Food Sciences, Faculty of Agricultural Engineering, Damascus University, with the aim of studying the antioxidant activity and biologically active compounds of licorice root extract, and studying the effect of treating fresh chicken breast meat with ethanolic extract of licorice root on some chemical and microbial indicators during cold storage at a temperature 4 ° C for a period of (16 days). Chicken breast meat samples were treated with concentrations (0, 0.25, 0.5, 0.75%) of the extract. The results showed that the treatment with these extracts led to a significant decrease in the moisture content and a significant increase in the proportions of ash, fat and protein compared to the control sample, and the treatments showed a significant decrease in the values of thiobarbituric acid (TBARS). On the other hand, the meat during cold storage showed a decrease in the value of pH compared to control, and a decrease in the general number of bacteria and the number of yeasts and fungi when treated with the ethanol extract, and this decrease was proportional to the increase in the concentration of the extract, and the absence of coliform growth was observed in all the treated samples, The treatment with the ethanolic extract of licorice root at a concentration of (0.75%) achieved the highest antioxidant activity, the highest oxidative stability of the meat through the highest low value (TBARS) and the highest inhibitory capacity for microbial growth, and The ethanolic extract also achieved an IC50 value (147.26) μg /ml and a total phenol content (113.19) mg gallic acid equivalent / g.